FAKTOR PENENTU PERILAKU AMAN PETANI DALAM PENGGUNAAN PESTISIDA BERDASARKAN HEALTH BELIEF MODEL : STUDI LITERATUR - Muhamad Agam Fadel Kurniawan; Bina Kurniawan; Suroto Suroto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Agriculture is one of the most hazardous occupational sectors, with a high prevalence of occupational injuries and work-related health problems. The risk of being exposed to pesticides is very much related to farmer’s behavior in using pesticides. Farmer's safe behavior is influenced by many factors. This study studied and analyzed the literature on factors related to farmer’s safe behavior in the use of pesticides based on the Health Belief Model. The method used in this research was the study of literature. In the relevant article obtained from Springer Link, Science Direct and Google Scholar databases in the last 10 years (2010-2020). This research was conducted in 10 international articles. The results of the 10 articles showed that farmers' safe behavior is influenced by demographic factors (age, education level, economic status, health experience) and perception factors (benefits, barrier, susceptibility, severity, self-efficacy). Therefore, external stimulus and training is one of the actions to change the perception and behavior of farmers in the use of pesticides.